VIRAL MARKETING DAN KEPUTUSAN PEMBELIAN KONSUMEN: KEPERCAYAAN SEBAGAI VARIABEL MODERASI - Sejati, Sugeng Waluyo; Silintowe, Yunita Budi Rahayu (PT Naureen Digital Education, 2024)
This study aimed to analyze the influence of viral marketing on purchasing decisions with trust as a moderating variable. This study used a quantitative approach using primary data. The distribution of questionnaires in this study used Google Forms, and the sample used was 105 respondents with purposive sampling technique. Descriptive statistical analysis techniques were used to analyze the data, and SPSS version 25 software was used to process the data. This study used simple regression analysis and moderated regression analysis (MRA). The results of this study indicate that viral marketing has a positive and significant effect on purchasing decisions. Meanwhile, testing the moderating variable states that trust cannot moderate the relationship between viral marketing and purchasing decisions.